Personality Traits in the Patients of Depression with Suicidal Ideation - Hassan, Sadia; Kumari, Darshana; Rehman, Faiza; Ayub, Muhammad (Indus Journal of Bioscience Research, 2025)
Introduction: Suicide is a major global health concern. Personality traits significantly influence depression with suicidal ideation, highlighting the need to explore their role for targeted, personalized treatment approaches. Objective: To assess the mean score of personality traits using Big Five Inventory 10 (BFI-10), in patients of depressive disorder with suicidal ideation presenting at the Department of Psychiatry and Behavioral Sciences, Jinnah Post Graduate Medical Centre (JPMC), Karachi. Study design: Cross sectional study. Study setting: Study was conducted at the Department of Psychiatry and Behavioral Sciences, JPMC, Karachi. Duration of study: 11th September, 2024 to 31st January, 2025. Subjects and methods: The Data was prospectively collected from patients after taking a written consent. One hundred patients who met the diagnostic criteria were included. A brief history was taken and demographic information was recorded after taking written informed consent. Data was analyzed by using SPSS 23.0. Effect modifiers were controlled through stratification to see the effect of these on the outcome variable. Post stratification independent t-test and one way ANOVA test was applied taking p-value of ≤0.05 as significant. Results: A total of 100 patients who met the inclusion and exclusion criteria were included in this study. Mean Age was 32 + 12 years. Mean scores of big Five personality traits were 5.94 ± 2.53, 3.62 ± 1.57, 4.02 ± 1.56, 4.68± 1.56, 4.96 ± 1.54, for Neuroticism, Extraversion, conscientiousness, openness to experience and Agreeableness respectively. Conclusion: Personality traits may significantly influence suicide risk, emphasizing the need for close monitoring and regular follow-up in vulnerable patients.